Some remarks on the coupling prescription of teleparallel gravity - Mosna, R. A.; Pereira, J. G. (Kluwer Academic/plenum Publ, 2004)
By using a nonholonomic moving frame version of the general covariance principle, an active version of the equivalence principle, an analysis of the gravitational coupling prescription of teleparallel gravity is made. It is shown that the coupling prescription determined by this principle is always equivalent with the corresponding prescription of general relativity, even in the presence of fermions. An application to the case of a Dirac spinor is made.
Keywords: teleparallel gravity; gravitational coupling; spinor fields; Dirac equation